1991
DOI: 10.1007/bf00764089
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable spreading behavior of molybdena on silica catalysts. Anin situ EXAFS-Raman study

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
0
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 25 publications
9
100
0
2
Order By: Relevance
“…2 -5 A number of studies have been published on the structure of supported molybdenum oxide on Al 2 O 3 using Raman spectroscopy, Fourier transform infrared (FTIR) spectroscopy, 95 Mo-NMR, extended x-ray absorption fine structure/nearedge structure (EXAFS/XANES) and XPS, but the structure is still a matter of debate. Konigsbarger et al 6 showed that there are at least three types of MoO 3 phase-tetrahedraland octahedral-coordinated surface phases and a crystalline phase. Leliveld et al 7 described small molybdenum oxide particles possessing a highly distorted octahedral structure with one terminal Mo O bond and 5-6-fold oxygen coordination ranging from 1.71 to 1.95Å.…”
Section: Introductionmentioning
confidence: 99%
“…2 -5 A number of studies have been published on the structure of supported molybdenum oxide on Al 2 O 3 using Raman spectroscopy, Fourier transform infrared (FTIR) spectroscopy, 95 Mo-NMR, extended x-ray absorption fine structure/nearedge structure (EXAFS/XANES) and XPS, but the structure is still a matter of debate. Konigsbarger et al 6 showed that there are at least three types of MoO 3 phase-tetrahedraland octahedral-coordinated surface phases and a crystalline phase. Leliveld et al 7 described small molybdenum oxide particles possessing a highly distorted octahedral structure with one terminal Mo O bond and 5-6-fold oxygen coordination ranging from 1.71 to 1.95Å.…”
Section: Introductionmentioning
confidence: 99%
“…in ambient environment) [16,17]. Heating the catalyst during the calcination converts polymolybdate to an isolated monodispersed Mo 6+ species [18]. The polymolybdate cluster is reformed after rehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Polymolybdate, such as heptamolybdate, was identified by Raman spectroscopy for the hydrated state of the catalyst [15][16][17]. Upon dehydration by thermal heating, spreading of Mo species occurs and yields isolated Mo 6+ species [18].…”
Section: Introductionmentioning
confidence: 99%
“…are recognized as industrially important catalysts for numerous chemical reactions [1][2][3][4][5][6][7][8][9][10][11]. For example, these catalysts are utilized for o-xylene oxidation to phthalic anhydride [12,13], methane/methanol oxidation to formaldehyde [14], and selective catalytic reduction (SCR) of NO with ammonia to N 2 over supported vanadia catalysts [15][16][17][18][19]; SCR of NO with ammonia and selective oxidation of methane over supported molybdena catalysts [20][21][22]; olefin metathesis and hydrocarbon isomerization reactions over tungsta catalysts; and metathesis of olefins and alkanes over supported rhenia catalysts [23][24][25]. These supported metal oxide catalysts consist of highly dispersed surface metal oxide species -the catalytic active sites -anchored to the underlying oxide support.…”
Section: Introductionmentioning
confidence: 99%